Motivating English Learners in Remote Areas: An Exploration of Teacher Roles and Classroom Strategies - Hanifa; Chairil Anwar Korompot; Muhammad Arham Basri (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study aims to explore the role of teachers in enhancing students’ motivation toward English learning in a remote area of Papua characterized by educational disparities. The study was conducted at SMA Negeri 1 Teminabuan, Sorong Selatan Regency, Southwest Papua, where limited facilities, technology, and exposure to English present significant challenges. Data were collected through semi-structured interviews with three English teachers and three students, classroom observations, and documentation. The data were analyzed using Miles & Huberman’s (1994) interactive model, involving data reduction, data display, and conclusion drawing/verification. The findings reveal that students’ motivation is influenced by internal factors (interest, goals, and self-efficacy), affective factors (confidence, anxiety, and fear of mistakes), cognitive factors (limited vocabulary and grammar), as well as external factors including family support, peer influence, and school resources. Teachers played a crucial role as facilitators and motivators, employing strategies such as providing encouragement, connecting English learning with students’ daily lives, and creating supportive classroom atmospheres. However, teachers faced multidimensional challenges, including limited facilities, minimal parental involvement, students’ lack of exposure to English, and the difficulty of balancing cultural identity with English learning. Despite these challenges, teachers demonstrated adaptability through contextual learning, creative teaching methods, and culturally responsive strategies that helped sustain students’ motivation. This study concludes that the role of teachers is central in bridging the gap created by educational disparities and that enhancing student motivation in remote areas requires both pedagogical innovation and systemic support. The study recommends targeted professional development for teachers and improved resource allocation to strengthen English education in disadvantaged regions.Keywords: Teacher role, Students motivation, English learning, remote areas, educational disparity, Papua